Current understanding and perspectives in anaerobic digestion based on genome-resolved metagenomic approaches. (January 2022) - Kim, Na-Kyung; Lee, Sang-Hoon; Kim, Yonghoon; Park, Hee-Deung
Graphical abstract: Highlights: Metagenomics to explore microbial metabolism in anaerobic digestion were reviewed. Community and functional dynamics of microbes in anaerobic digestion were reviewed. Gene-centric and genome-centric metagenomic approaches were compared. Metabolic functions in response to the types of anaerobic digestion were compared. Perspectives for genome-centric applications in anaerobic digestion are outlined. Abstract: Anaerobic digestion (AD) is a technique that can be used to treat high concentrations of various organic wastes using a consortium of functionally diverse microorganisms under anaerobic conditions. Methane gas, a beneficial by-product of the AD process, is a renewable energy source that can replace fossil fuels following purification. However, detailed functional roles and metabolic interactions between microbial populations involved in organic waste removal and methanogenesis are yet to be known. Recent metagenomic approaches based on advanced high-throughput sequencing techniques have enabled the exploration of holistic microbial taxonomy and functionality of complex microbial populations involved in the AD process. Gene-centric and genome-centric analyses based on metagenome-assembled genomes are a platform that can be used to study the composition of microbial communities and their roles during AD. This review looks at how these up-to-date metagenomic analyses can be applied to promote our understanding and improved the development of the AD process.